Analyzing Barito River Channel Management's Policy Implementation in Using Natural Potentials to Increase Income - Gazali, Zulfadli; Ilham, Muh.; Effendy, Khasan; Labolo, Muhadam (International Journal Labs, 2023)
The purpose of this research is to analyze and find out the implementation, constraints in the process and strategies that can be used as a solution to the obstacles in the policy process for managing the Barito River Channel in exploiting natural potential as an increase in income in the Province of South Kalimantan. This study uses the theory of policy implementation put forward by Grindle which consists of policy content and policy context. The research method used is a qualitative approach with a descriptive research type. Informants in this study as many as 10 people. The data analysis technique used is data reduction, data display, and conclusion. The results showed that the implementation of the Barito river channel management policy in exploiting natural potential as an increase in income for the Province of South Kalimantan had been carried out properly and PT. Ambapers will obtain a concession for the next 20 years. To increase revenue, a strategy is needed to explore potential levy objects, renegotiate the profit-sharing system with partner companies, develop lanes in the Barito River Channel so that ships with a larger capacity can pass through, develop tourism potential in the Barito River Channel. Barito River, developing a new business in the field of boat rental, developing a business in the accommodation and lodging sector for crew members operating in the Barito River Channel, and developing shipping lanes in the Barito River Channel up to the province of Central Kalimantan.